2019
DOI: 10.4236/ojpsych.2019.92010
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress, Coping Strategies, and Quality of Life among Nurses in General and Psychiatric Setting in Jeddah City—KSA

Abstract: Purpose: This study is aimed at comparing the level of occupational stress, ways of coping and the quality of life among nurses. Methods: Descriptive explanatory design was used with 278 nurses working in King Abdul Aziz Hospital in Jeddah, Mental Health Hospital in Jeddah, and Dr. Suleiman Fakeeh Hospital in Jeddah. Findings: Psychiatric nurses experience greater occupational stress than general nurses (p = 0.001). There was no statistically significant difference between the psychiatric and general nurses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…Alharbi and Alshehry (2019) conducted a cross‐sectional study to assess occupational stress among nurses in Riyadh, Saudi Arabia, and found that almost all the respondents had been exposed to several occupational stressors in the previous month. Their findings were consistent with the study findings of Alharbi and Hasan (2019), who conducted their study at a different location in Saudi Arabia.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…Alharbi and Alshehry (2019) conducted a cross‐sectional study to assess occupational stress among nurses in Riyadh, Saudi Arabia, and found that almost all the respondents had been exposed to several occupational stressors in the previous month. Their findings were consistent with the study findings of Alharbi and Hasan (2019), who conducted their study at a different location in Saudi Arabia.…”
Section: Introductionsupporting
confidence: 92%
“…Based on our findings, nurses' perception of occupational stress was moderate. This finding has been extensively reported in several studies in Saudi Arabia in different healthcare settings, such as intensive care units (Alharbi & Alshehry, 2019; Batran, 2019), palliative care units (Miligi et al, 2019), acute care units (Almazan et al, 2019; Rayan et al, 2019), psychiatric units (Alharbi & Hasan, 2019), and primary care units (Al‐Makhaita et al, 2014). Most of these studies linked these findings to the chronic shortage of nurses in Saudi Arabia and consequently supported the need for a reassessment of the nursing policy (Alsufyani et al, 2021).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations